Growth and Yield of Soybean as a Response of the Fertilization of NPK Compound Produced with Spent and Deoiled Bleaching Earth Filler - Radinal Arief Sinaga; Budiastuti Kurniasih; Eka Tarwaca Susila Putra (Universitas Sebelas Maret, 2021)
Spent Bleaching Earth (SBE) is a by-product of the refining of Crude Palm Oil (CPO) into cooking oil which is classified as hazardous and toxic materials waste. SBE has the potential to be used as a filler in the production of NPK fertilizer. This study aims to compare the effect of SBE and Deoiled Bleaching Earth (DBE) as the replacement of clay mineral, which is expected to have the same effect as the control treatment in terms of the leaf area, total dry weight, plant height and yield of plant. This experiment used a one-factor Randomized Complete Block Design (RCBD) with three replicates. The treatments of filler in NPK fertilizer were 10% clay minerals, NPK with 5% clay mineral + 5% SBE filler and NPK with 5% clay mineral + 5% DBE filler. Fertilizer was given twice, ie when the plant was 14 days after planting (DAP) as much as 2 g polybag-1 and age 35 DAP as much as 3 g polybag-1 at each treatment. The results showed that the application of NPK fertilization with 5% clay mineral + 5% SBE filler and NPK fertilization with 5% clay mineral + 5% DBE filler had the same effect as NPK fertilization with 10% clay mineral filler on leaf area, total dry weight, plant height and yield of plant. SBE and DBE can be used as substituties for clay mineral in NPK fertilizer production.